2022
DOI: 10.1002/adom.202201462
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Paper and Time Temperature Integrators Made From a Structural Colored Polymer Crosslinked With Hydrogen Bonded Cyclohexanoic Acid Derivatives

Abstract: Hydrogen‐bonded cyclohexanoic derivatives are applied in a structural colored cholesteric liquid crystal (CLC) helical polymer that demonstrates an extraordinary dual thermal response. Integration of the dynamic hydrogen‐bonded cyclohexanoic acid derivatives in the CLC polymer as supramolecular crosslinks yields an immediate and irreversible loss of the green structural color upon exposure to temperatures above the cholesteric‐to‐isotropic transition temperature (TNI) caused by the helical order loss. Exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…44−47 As another example, consider CTC-LCEs acting first as soft actuators and later repurposed as reusable optical sensors (Figures S15 and S16). 48,49 Our results show that merging the self-assembly of molecules and supramolecular polymers results in a new class of interactive, sustainable materials with coupled and gated responses.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…44−47 As another example, consider CTC-LCEs acting first as soft actuators and later repurposed as reusable optical sensors (Figures S15 and S16). 48,49 Our results show that merging the self-assembly of molecules and supramolecular polymers results in a new class of interactive, sustainable materials with coupled and gated responses.…”
Section: Discussionmentioning
confidence: 79%
“…The (re)­configuring of materials into different forms and performing new functions could help reduce the generation of waste that becomes space junk. As another example, consider CTC-LCEs acting first as soft actuators and later repurposed as reusable optical sensors (Figures S15 and S16). , Our results show that merging the self-assembly of molecules and supramolecular polymers results in a new class of interactive, sustainable materials with coupled and gated responses.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of the ink on the substrate was realized through the gelling interaction between borax and guar gum. Foelen et al 65 reported a TTI prototype by inkjet printing cholesteric liquid crystal polymers with dual thermal responsiveness.…”
Section: Development Trend Of Ttismentioning
confidence: 99%
“…The attachment of the ink on the substrate was realized through the gelling interaction between borax and guar gum. Foelen et al65 reported a TTI prototype by inkjet printing cholesteric liquid crystal polymers with dual thermal responsiveness.5 | APPLICATIONS OF TTIS5.1 | MeatMeats are significant nutrients of human's dietary structure, whose safety and quality are frequently secured by cold chain transportation.Meat transportation is involved with different temperature requirements, for example, frozen (below À18 C) and chilled (4 C-8 C) transportations 66. Keeping at a low temperature has always challenged the long-term performance of TTIs used in the frozen transportation.…”
mentioning
confidence: 99%
“…The corresponding LCEs, named LCE-COOH and LCE-OH, contain the functionalized chain extenders and dodecylamine in a 1:1 ratio, whereas an LCE with only dodecylamine chain extender (LCE-C 12 ; no ability to form hydrogen bonds) is used as a reference. The COOH groups are known to form relatively strong hydrogen-bonded dimers [69][70][71][72] while the aliphatic hydroxyl groups are anticipated to form very weak contacts. [73] Disperse Red 1 (DR1) was added to the polymerizable mixtures at 1 wt% concentration to enable photothermal actuation of the LCEs.…”
Section: The Design Conceptmentioning
confidence: 99%